Faktor yang Berhubungan dengan Kebiasaan Merokok Pada Remaja di Desa Soga Kabupaten Soppeng - Erlani, Erlani; Lutfiyyah, Lutfiyyah; Rasman, Rasman (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Based on the Indonesian Health Survey (SKI) conducted in 2023, it is estimated that there are around 70 million active smokers in Indonesia. One of the most concerning findings from this survey is the significant increase in the number of smokers among children and adolescents, indicating that younger age groups are becoming more vulnerable to tobacco use. This study aims to identify the factors that influence smoking habits among adolescents in Soga Village, located in Soppeng Regency. The type of research is observational analytic with a cross-sectional design. The population in this study were all male adolescents in Soga Village, Soppeng Regency, totaling 200 adolescents. The sampling technique used purposive sampling with a total sample of 133 people. The results showed that there was a relationship between easy access to cigarettes with smoking habits in adolescents with a p-value of 0.005 < 0.05, there was no relationship between friends with smoking habits in adolescents with a p-value of 0.596 > 0.05, there was a relationship between knowledge and smoking with a p-value of 0.001 < 0.05, there was no relationship between advertising promotion as a factor triggering smoking habits with a p-value of 0.265 > 0.05, there was a family relationship with smoking with a p-value of 0.005 < 0.05 and there was a relationship between cigarette addiction with smoking habits with a p-value of 0.001 < 0.05. The conclusion in the study is that the factors that trigger adolescent smoking habits are access to cigarettes, knowledge, family and smoking addiction. It is recommended that adolescents divert activities to more useful activities such as sports, arts, or youth organizations in the village so that free time is not filled with smoking behavior.